2020
DOI: 10.1097/phh.0000000000001278
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Accreditation on Health Department Financial Resources

Abstract: Context:There is limited data available on the financial benefits of public health accreditation.Objective: This study assessed the financial impacts reported by public health departments as a result of participating in the Public Health Accreditation Board (PHAB) national accreditation program. Design: Data from an ongoing survey of outcomes among health departments accredited for 1 year were linked to PHAB administrative data on health department characteristics to examine self-reported financial impacts of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…11,12 Studies demonstrate the potential that PHAB accreditation has to transform PH practice and improve PH agency capabilities to deliver essential PH services. 13,14 For example, benefits regarding performance management, quality improvement, accountability, and transparency have been associated with accreditation, [15][16][17][18] as well as areas of practice such as resource planning, 19 community engagement, 15,20 and the ability to identify and address gaps in workforce development. 15 Despite these benefits, a majority of LHDs have not been accredited yet in this relatively new process in which the first agencies were accredited in 2013.…”
mentioning
confidence: 99%
“…11,12 Studies demonstrate the potential that PHAB accreditation has to transform PH practice and improve PH agency capabilities to deliver essential PH services. 13,14 For example, benefits regarding performance management, quality improvement, accountability, and transparency have been associated with accreditation, [15][16][17][18] as well as areas of practice such as resource planning, 19 community engagement, 15,20 and the ability to identify and address gaps in workforce development. 15 Despite these benefits, a majority of LHDs have not been accredited yet in this relatively new process in which the first agencies were accredited in 2013.…”
mentioning
confidence: 99%
“…11 Studies have found that accredited LHDs were more likely to report higher capacity for evidence-based decision making and evaluation than health departments that were not yet preparing for PHAB accreditation, 12 and accredited LHDs are more likely to report new funding as a result of accreditation, improved staff competencies, and new opportunities for partnerships and collaboration. 13 Given the barriers to applying and the relatively low rate of application for accreditation among smaller LHDs, there is a need to explore how the experiences and benefits of accreditation differ across LHDs of different sizes. This study sought to explore the benefits of accreditation reported by LHDs after becoming accreditation and compare the experiences of small LHDs with medium and large LHDs.…”
mentioning
confidence: 99%
“…These include improved and implemented new quality improvement (QI) and performance management efforts; strengthened partnerships; improved internal and external transparency and accountability; improved workforce training and development; and improved utilization of resources 11. Studies have found that accredited LHDs were more likely to report higher capacity for evidence-based decision making and evaluation than health departments that were not yet preparing for PHAB accreditation,12 and accredited LHDs are more likely to report new funding as a result of accreditation, improved staff competencies, and new opportunities for partnerships and collaboration 13…”
mentioning
confidence: 99%